GE_GERICHTE C/12221/2006 vom 14. Dezember 2007 - GE Cour de justice (2007)
; FAITS NOUVEAUX ; OBLIGATION D'ENTRETIEN ; PRÉVOYANCE PROFESSIONNELLE ; IMPÔT | CO.143 CO.148 CC.125.8 CC.138 CC.163 LIPP.12 LPC.10 LPC.308.2 LPC.394.2